Efektivitas Konsentrasi Biopestisida Asap Cair Tandan Kosong Kelapa Sawit (Elaeis guineensis Jacq.) terhadap Mortalitas Hama Uret Tebu (Lepidiota Stigma F.) - Bachri, Firza Suryansya; Irawan, Triono Bambang (Agropross : National Conference Proceedings of Agriculture, 2023)
Indonesia’s The sugarcane white grub (Lepidiota stigma F.) is one of the pests that causes a decrease in sugarcane production. There are several ways to control pests, one of which is using biopesticide made from the liquid smoke of empty oil palm bunches. This research was conducted in January-February 2023 at the Plant Protection Laboratory of the Department of Agricultural Production at Jember State Polytechnic. The aim of this study was to determine the effectiveness of different concentrations of biopesticide made from the liquid smoke of empty oil palm bunches in controlling the sugarcane white grub. The study used a randomized block design (RBD) consisting of four treatments with six replications, namely 1% concentration, 1.5% concentration, 2% concentration, and 2.5% concentration of biopesticide made from the liquid smoke of empty oil palm bunches. The data were analyzed using ANOVA, and if significant effects were found, further analysis was conducted using the Tukey test at a significance level of 5%. The LT50 was determined using probit analysis. The parameters used were mortality, physical changes, and LT50. The results showed that the biopesticide made from the liquid smoke of empty oil palm bunches had a highly significant effect on the mortality of the sugarcane white grub, with the fastest LT50 value of 98 hours at a concentration of 2.5%.